Update on the mechanism of microglia involvement in post-stroke cognitive impairment - Zeng, Tianxiang; Liu, Jun; Zhang, Wenjun; Yu, Yanyan; Ye, Xinyun; Huang, Qianliang; Li, Peng; Jiang, Qiuhua (Frontiers in Aging Neuroscience, 2024)
Post-stroke cognitive impairment (PSCI) is a clinical syndrome characterized by cognitive deficits that manifest following a stroke and persist for up to 6 months post-event. This condition is grave, severely compromising patient quality of life and longevity, while also imposing substantial economic burdens on societies worldwide. Despite significant advancements in identifying risk factors for PSCI, research into its underlying mechanisms and therapeutic interventions remains inadequate. Microglia, the brain’s primary immune effector cells, are pivotal in maintaining, nurturing, defending, and repairing neuronal function, a process intrinsically linked to PSCI’s progression. Thus, investigating microglial activation and mechanisms in PSCI is crucial. This paper aims to foster new preventive and therapeutic approaches for PSCI by elucidating the roles, mechanisms, and characteristics of microglia in the condition.